Large D-Dimer Fluctuation in Normal Pregnancy: A Longitudinal Cohort Study of 4,117 Samples from 714 Healthy Danish Women - Katrine K. Hedengran; Malene R. Andersen; Steen Stender; Pal B. Szecsi (Obstetrics and Gynecology International)
Introduction. D-dimer levels increase throughout pregnancy, hampering the usefulness of the conventional threshold for dismissing thromboembolism. This study investigates the biological fluctuation of D-dimer in normal pregnancy. Methods. A total of 801 healthy women with expected normal pregnancies were recruited. D-dimer was repeatedly measured during pregnancy, at active labor, and on the first and second postpartum days. Percentiles for each gestational week were calculated. Each individual D-dimer was normalized by transformation into percentiles for the relevant gestational age or delivery group. The range in percentage points during the pregnancy and the delivery was calculated, and reference intervals were calculated for each pregnancy trimester, during vaginal delivery and scheduled and emergency cesarean section, and for the first and second day postpartum. Results. D-dimer increased during pregnancy; the maximal fluctuation was approximately 20 percentile points in approximately half of the women. In one out of ten women, the D-dimer values fluctuated by more than 50 percentile points. Conclusions. Due to the biological variation in D-dimer within each individual woman during normal pregnancy, repeated D-dimer measurements are of no clinical use in the evaluation of thromboembolic events during pregnancy.